(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The Authors express comments regarding the presence of unguarded domestic ruminants in alpine environment, highlighting the potential criminal responsibilities of the owners and trying to bring in the issue of the proper legal category of these specimens.